Impact of stacking order and annealing temperature on properties of CZTS thin films and solar cell performance. (December 2021) - Olgar, M.A.; Sarp, A.O.; Seyhan, A.; Zan, R.
Abstract: In this study, Cu2 ZnSnS4 (CZTS) thin films were synthesized by a two-stage process. In the first stage, CuSn/Zn/Cu (E-type) and CuSn/ZnS/Cu (B-type) stacked films were formed using the sputtering method. In the second stage, precursor films were annealed in sulfur atmosphere utilizing various annealing temperatures (500, 525, 550 and 575 °C) employing the Rapid Thermal Processing (RTP) method. The EDX measurements demonstrated that almost all the samples had Cu-poor and Zn-rich compositions, as targeted. The XRD patterns of all the CZTS samples were dominated by diffraction peaks of the kesterite CZTS phase. In addition to CZTS phase, Cu–S/Sn–S based secondary phases in all E-type CZTS thin films and some B-type CZTS samples annealed at lower temperatures (500 and 525 °C) were observed. The samples annealed at above 525 °C revealed purer crystal structure in terms of secondary phases and they have more promising crystallite size in both types of CZTS thin films. The Raman spectroscopy measurements confirmed the formation of kesterite CZTS phase and distinguished the formation of Cu2 SnS3 (CTS) phase for some samples. The samples annealed at 550 °C presented purer structure for potential solar cell application. The SEM surface and cross-section images of all CZTS samples displayed dense and polycrystalline structures but samples annealed at 550 °C presented a larger-grained surface and cross-section structure in both types of CZTS films. PL spectra of the B-type CZTS samples exhibited a purer band structure with respect to E type CZTS samples according to their PL band values. The best solar cell performance was achieved with CZTS thin film prepared using CuSn/ZnS/Cu stack annealed at 550 °C temperature with 252 mV, 32 mA/cm 2, and 3.79% parameters. Highlights: CuSn/Zn/Cu and CuSn/ZnS/Cu stacks were used for fabrication of CZTS thin film. Impact of stacking order and annealing temperature was investigated. CZTS phase was observed in all the samples regardless of growth parameters. Formation of CuS, SnS2 and CTS secondary phases was observed in some samples. The best cell was obtained by CZTS using CuSn/ZnS/Cu annealed at 550 °C with 3.79%.